Short-term effects of angiotensin receptor blockers on blood pressure control, and plasma inflammatory and fibrinolytic parameters in patients taking angiotensin-converting enzyme inhibitors - ÇİNÇİN, AHMET ALTUĞ (J R A A S LTD, 2008)
Introduction. Angiotensin-converting enzyme (ACE) inhibitors reduce cardiovascular events in patients with established vascular disease and heart failure (HF). ACE-inhibitors have important effects on fibrinolytic balance, which may be the underlying mechanism for a reduction in cardiovascular events. Although angiotensin receptor blockers (ARBs) offer greater tolerability than ACE-inhibitors, the major ARB trials have demonstrated a lack of reduction in myocardial infarction (MI) occurrence and mortality in contrast to ACE-inhibitors. In this study, we investigated the combined effects of ARBs and ACE-inhibitors on fibrinolytic and inflammatory parameters in patients with uncontrolled hypertension. Methods. Twenty-four patients with uncontrolled hypertension despite taking adequate doses of ACE-inhibitor therapy were selected. Patients were started on Candesartan 16 mg once a day. Plasma plasminogen activator inhibitor (PAI-1) antigen (Ag), tissue plasminogen activator (t-PA) Ag, thrombin-activatable fibrinolysis inhibitor (TAFI) % activity and high sensitivity C-reactive protein (hsCRP) levels, were measured during low salt intake at baseline and two weeks after therapy with an ARB. Results. Addition of ARB to the regimen reduced systolic (155 17 vs. 139 13, p<0.001), and diastolic (91 9 vs. 81 8, p<0.001) blood pressures (BP). No significant changes were observed in PAI-1 Ag (66 51 vs. 68 52, p=0.9), t-PA Ag (12.6 +/- 5.3 vs. 13.3 +/- 4.7, p=0.3),TAFI % activity 119 +/- 30 vs. 118 +/- 32, p=0.9) and hsCRP (3.9 +/- 3.4 vs. 3.6 +/- 3.6, p=0.7) levels after adding an ARB. Conclusions. Combined ARB and ACE-inhibitor use provide better BP control without any detrimental effect in plasma inflammatory and fibrinolytic parameters.
Keywords: angiotensin-converting enzyme inhibitor; angiotensin receptor blocker; high sensitive C-reactive protein; hypertension; plasma plasminogen activator inhibitor; tissue plasminogen activator; PLASMINOGEN-ACTIVATOR INHIBITOR-1; CORONARY-ARTERY-DISEASE; MYOCARDIAL-INFARCTION; CARDIOVASCULAR EVENTS; RANDOMIZED-TRIAL; HEART-FAILURE; HYPERTENSIVE PATIENTS; ENDOTHELIAL-CELLS; DOUBLE-BLIND; RISK